2004
DOI: 10.1207/s15374424jccp3302_2
|View full text |Cite
|
Sign up to set email alerts
|

Temperament, Anxiety, and Depression: Comparisons Across Five Ethnic Groups of Children

Abstract: Extending analyses from a large school-based sample of children and adolescents (N = 1,126; Chorpita, 2002), this study examined anxiety and depression assessment with 5 ethnic groups in Hawaii. Ethnic differences in anxiety and depression symptoms, along with 2 temperamental characteristics-negative affectivity (NA) and positive affectivity (PA)-were examined within the context of the tripartite model of anxiety and depression (Clark & Watson, 1991). Minimal between-group differences in temperamental characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 42 publications
7
50
0
Order By: Relevance
“…Although administration of a structured interview to establish diagnoses would represent a methodological improvement, the validity of the self-report measures used in this study is well-established. Furthermore, virtually all studies of racial/ethnic differences in adolescent symptomatology have relied on self-report measures (e.g., Austin and Chorpita 2004;Cole et al 1998;Roberts et al 1997). Nonetheless, epidemiologic studies of diagnosed psychiatric disorders among adolescents should be conducted with a particular focus on examining differences in prevalence and incidence across racial/ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although administration of a structured interview to establish diagnoses would represent a methodological improvement, the validity of the self-report measures used in this study is well-established. Furthermore, virtually all studies of racial/ethnic differences in adolescent symptomatology have relied on self-report measures (e.g., Austin and Chorpita 2004;Cole et al 1998;Roberts et al 1997). Nonetheless, epidemiologic studies of diagnosed psychiatric disorders among adolescents should be conducted with a particular focus on examining differences in prevalence and incidence across racial/ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these studies examined frequency and intensity of common fears and reported variability across racial/ethnic groups (Ollendick et al 1996;Shore and Rappaport 1998) with White children reporting the lowest levels of fear. A large study conducted in Hawaii reported significant group differences in the prevalence of symptoms of separation anxiety disorder, panic disorder, social anxiety, and obsessivecompulsive disorder (Austin and Chorpita 2004) with White children generally endorsing lower levels of symptoms than other groups (Filipino, Native Hawaiian, and Asian American). Three other studies have reported racial/ethnic differences in anxiety symptoms among clinical of children and adolescents seeking treatment for an anxiety disorder Ginsburg and Silverman 1996;Pina and Silverman 2004).…”
Section: Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the age distribution was as follows: 18.9, 19.7, 16.8, 16, 11.3, 11.8 and 5.5% for age 8,9,10,11,12,13, and 14 respectively. From this total sample, 75.7% (n = 184) participated in wave 2 and 24.3% (n = 59) did not participate in wave 2.…”
Section: Referred Samplementioning
confidence: 99%
“…Research supports the role of negative affectivity being positively related to anxiety and depression and low positive affectivity (i.e., anhedonia) being related to depression (e.g., Austin and Chorpita 2004;Chorpita 2002;Chorpita and Daleiden 2002;Chorpita et al 2000a;Lambert et al 2004). For example, Jacques and Mash (2004) examined the relationships between positive and negative affectivity and anxiety and depression in a sample of elementary and high school aged boys and girls (n = 472) and found general support using structural equation modeling (SEM).…”
Section: Positive and Negative Affectivitymentioning
confidence: 99%